Synthesis and Evaluation of Novel Naphthenate Inhibitor Demulsifier from Fatty Hydrazide Derivatives - Borhan, N.; Ramli, A.; K. Salleh, I. (International Journal of Engineering and Technology, 2019)
The production of crude oil contained Alkaline-Surfactant-Polymer (ASP)-chemical enhance oil recovery (CEOR) has a significant detrimental effect on flow assurance mainly for formation of microemulsion which is thermally stable and difficult to break and separated into clean crude oil and water phase. Quality of clean crude oil for saleability is important through achievement of crude oil dehydration in terms of basic sediment and water (BS&W) specification less than 0.5%.Â  This paper outlines a case-study where stable microemulsions were formed following mixing of crude oil and ASP brine, requiring operationally intensive remediation. Finally, novel palm oil-derived fatty hydrazide Naphthenate Inhibitor (NI)-Demulsifier were synthesized, formulated and tested using dynamic laboratory tests using a multifunctional mini flow loop (MMFL). Under dynamic laboratory test, crude oil, prepared produced water and ASP were mixed under high shear at separator temperature and pressure. The NI-demulsifiers chemical injection was carried out after microemulsions were formed before the separator, representing a wellhead injection point and for a sufficient time to allow the microemulsion system to reach equilibrium. This work demonstrates the importance of considering the impact of ASP-EOR fluids on existing emulsion and using an appropriate laboratory technique to evaluate potential mitigating treatments for oil-water separation technology. The effects of temperature and water cut on microemulsion stability are shown and the NI-demulsifier demonstrated excellence in demulsifying and dehydration at minimal dosage.Â Â